Asymmetric Quantum Steering Generated by Triple-Photon Down-Conversion Process With Injected Signals - Chen, T. H.; Pan, K. Y.; Xiao, C.; Yu, Y. B.; Chen, A. X. (Frontiers in Physics, 2022)
Asymmetric quantum steering generated by triple-photon down-conversion process in an injected signals optical cavity is investigated. Triple-photon down-conversion process can be realized in an optical superlattice by quasi-phase-matching technology. Asymmetric quantum steering can be obtained in this triple-photon down-conversion process. The direction of asymmetric quantum steering can be controlled by adjusting the parameters of the nonlinear process. The generation of asymmetric quantum steering in present scheme has potential applications in quantum secret sharing and quantum networks.